2022
DOI: 10.1002/adts.202200226
|View full text |Cite
|
Sign up to set email alerts
|

Continual Learning Electrical Conduction in Resistive‐Switching‐Memory Materials

Abstract: The authors apply the concept of continual learning to modeling conductive‐filament growth in resistive‐switching materials (RSM). The approach permits computation of compliance current without knowing the geometries of conductive filaments and switching behaviors. This avoids the need to retrain the entire dataset when additional compliance currents are considered and is thus ideal for resistive switching (RS) thin films, doped layers, and other material systems. Computation of compliance current is consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…[148] The resistive switching is a result of the redox reaction and ion migration, which are induced by electric potentials, chemical potentials, and temperature gradients over reaction coordinates, in the general theory of the resistive switching process. [149][150][151][152][153] When ions are electrically or thermally stimulated, anions including oxygen ions or the corresponding oxygen vacancies become more movable compared to cations for various dielectric materials, such as perovskites and transition-metal oxides. The variation in the metal-cation valence in the dielectric material alters electrical conductivities when oxygen anions move toward the anode upon the application of an electric field (Figure 4a).…”
Section: Anion-based Switchingmentioning
confidence: 99%
“…[148] The resistive switching is a result of the redox reaction and ion migration, which are induced by electric potentials, chemical potentials, and temperature gradients over reaction coordinates, in the general theory of the resistive switching process. [149][150][151][152][153] When ions are electrically or thermally stimulated, anions including oxygen ions or the corresponding oxygen vacancies become more movable compared to cations for various dielectric materials, such as perovskites and transition-metal oxides. The variation in the metal-cation valence in the dielectric material alters electrical conductivities when oxygen anions move toward the anode upon the application of an electric field (Figure 4a).…”
Section: Anion-based Switchingmentioning
confidence: 99%
“…Currently, the focus for enhancing the speed and power performance of artificial intelligence tasks is on training, driven by DOI: 10.1002/apxr.202300085 the utilization of hardware accelerators for achieving machine-learning inference in deep neural networks (DNNs) . [1][2][3][4][5][6] Theoretical calculations have revealed that in-memory analogue computing using memristive crosspoint architecture result in a substantial energy, area and time benefit compared to that using a conventional digital complementary metal-oxide semiconductor (CMOS) system. [7][8][9][10][11][12] However, traditional memristive experimental studies have been constrained to reduced problem types.…”
Section: Introductionmentioning
confidence: 99%
“…Memristive hardware exhibits a small energy per conductance update, rapid switching time and excellent device miniaturization. [13][14][15][16][17][18] Computing and data storage have been achieved using memristive hardware through alterable conductance levels, which enables memory and processing to be combined in a parallel-based design. [19][20][21][22][23][24] Experiments have demonstrated the maximum number of distinct conductance levels utilized for neural-network (NN) learning for different memristive elements, e.g., resistive-switching memory (RSM) elements, magnetic-tunnelling memory (MTM) elements, ferroelectric memory (FM) elements, and other memory elements.…”
Section: Introductionmentioning
confidence: 99%